ANALISIS DAN IMPLEMENTASI KEAMANAN JARINGAN PADA PT. DAE MYUNG HIGHNESS INDONESIA - Alwafi, Fariz (LPPM Universitas Islam 45 Bekasi, 2015)
ABSTRACT VPN security with an attack (attacking) the method of Denial of Service (DOS) m Man-in-the-Middle (MITM) with ettercap and hacking with Backtrack Linux applications. The experimental results of testing connectivity to the conclusion that the bandwidth is a major factor merits network connectivity between offices. In experiments testing the VPN security, attack (hacking) to Denial of Service (DoS) was successfully shut down service or service on the VPN server. Security of data in a computer network is very important, especially confidential data. Currently there are several alternative methods for data security on the network, for example to encrypt the data before it is sent, install a firewall so that no external intruders who can get into the internal computer network and others. To overcome the problem of security in data communications on public networks. In general, the VPN is a local communication network connected via the public network, public infrastructure is the most widely used Internet network. Inside there is a combination of technology VPN tunneling and encryption to create a VPN into a reliable technology to solve security problems on the network. VPN itself is highly dependent on the stability of the Internet both in the server and the user, it is necessary to be equipped with the best ISP that provides Internet access speed and security are qualified to anticipate the attack to the VPN server. Keyword: VPN, connectivity, security, attacking. ABSTRAK Keamanan VPN dengan melakukan serangan (attacking) dengan metode Denial of Service (DOS) Man-in-the-Middle (MITM) dengan ettercap dan hacking dengan aplikasi Linux Backtrack. Hasil eksperimen pengujian konektivitas memberikan kesimpulan bahwa bandwidth merupakan faktor utama baik-buruknya konektivitas jaringan antar kantor. Pada eksperimen pengujian keamanan VPN, serangan (attacking) dengan Denial of Service (DoS) ternyata berkasil mematikan service atau layanan pada server VPN. Keamanan data pada sebuah jaringan komputer sangatlah penting, terutama data yang bersifat rahasia. Saat ini terdapat beberapa alternatif metode untuk keamanan data pada jaringan, misalnya dengan engenkripsi data sebelum dikirimkan, memasang firewall sehingga tidak ada penyusup dari luar yang dapat masuk ke jaringan komputer internal dan lain-lain. Untuk mengatasi masalah keamanan dalam komunikasi data pada jaringan umum. Secara umum VPN merupakan suatu jaringan komunikasi lokal yang terhubung melalui media jaringan publik, infrastruktur publik yang paling banyak digunakan adalah jaringan internet. Didalam VPN terdapat perpaduan teknologi tunneling dan enkripsi yang membuat VPN menjadi teknologi yang handal untuk mengatasi permasalahan keamanan didalam jaringan. VPN sendiri sangat tergantung pada kestabilan jaringan internet baik dari sisi Server maupun User, untuk itu perlu dibekali dengan ISP yang terbaik yang menyediakan kecepatan akses internet dan keamanan yang mumpuni guna mengantisipasi serangan kepada VPN Server. Kata Kunci : VPN, konektivitas, keamanan, attacking.